Wound healing property of paroxetine in immunosuppressed albino rats - S, Dwajani; Gurumurthy, Ranjana (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objectives of this study were to evaluate the wound healing activity of Paroxetine in different wound models in wistar rats and to study its effects on dexamethasone suppressed wound healing. Methods: For assessment of wound healing activity, excision and incision wound models were used. Group I was assigned as control, orally, Group II received Paroxetine, i.p, Group III received Dexamethasone intramuscularly (i.m) and Group IV received Dexamethasone i.m and Paroxetine, i.p. Parameters observed were epithelization and wound contraction of excision model and breaking strength of incision wound model. Results: In incision model, it was noted that the breaking strength was not significantly increased in paroxetine treated group when compared to control group. Paroxetine hastened the period of epithelization and the effect of dexamethasone was reversed by paroxetine in incision and excision models Conclusion: It is concluded that Paroxetine could be an effective agent for healing wounds in immunocompromised patients.